PHILIA AS FRIENDSHIP IN NICHOLAS SPARKS’ NOVEL THE LONGEST RIDE - Khafifah Aidhana Khairunnisa H.; M. Manugeren (Universitas Islam Sumatera Utara, 2021)
This study is aimed at analyzing Philia as friendship in Nicholas Sparks’ novel, The Longest Ride, published in 2013. The analysis is focused on the categories of Philia as friendship covering utility, happiness, and moral done by the major characters of the novel, namely Ira Levinson, Ruth, Luke Collins, Sophian Danko. The method used to analyze this study is a descriptive qualitative method. In this study, the researchers apply the theory of philia as friendship proposed by Aristotle. Philia is one type feeling of love in the Christian and Greek traditions based on friendly relations. Other types of love that are also in Christian theology are eros, agape and storage. The results show that the categories of Philia as friendship: utility, happiness and moral are reflected and done by the major characters. Utility is seen from Ira and Ruth with strong and healthy love relationship. Happiness is seen through Ira and Ruth who always feels happy when they see each other. Moral can be seen through the trust of Ira and Ruth who always share each and everything together.